1983
DOI: 10.1002/ana.410130618
|View full text |Cite
|
Sign up to set email alerts
|

Parental age as a risk factor in Alzheimer's disease

Abstract: Alzheimer's disease is the most common type of dementia, and it is characterized by a decline in memory or other thinking skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 5 publications
2
10
1
1
Order By: Relevance
“…To date, four stud-ies have reported such an association [4,29,44,451 and five have not [46][47][48][49][50]. Our study was also unable to replicate this finding, although fathers of patients were an average of 2 years older than fathers of control subjects; the statistical significance of this finding was suggestive ( p = 0.12).…”
Section: Parental Agecontrasting
confidence: 79%
“…To date, four stud-ies have reported such an association [4,29,44,451 and five have not [46][47][48][49][50]. Our study was also unable to replicate this finding, although fathers of patients were an average of 2 years older than fathers of control subjects; the statistical significance of this finding was suggestive ( p = 0.12).…”
Section: Parental Agecontrasting
confidence: 79%
“…The results of our study indicated the mean ages of the parents of AD patients and nondemented control subjects at the time of births did not differ, in accord with other groups' findings [15,20].…”
Section: Epidemiological Aspectssupporting
confidence: 79%
“…This study also showed that high birth order was more frequent in patients than in controls (even though the measure of association did not reach statistical significance). Other studies, however, found no association between advanced age of the mother at subject's birth and occurrence of AD (14,171.…”
Section: Ns S Ns Smentioning
confidence: 97%